Working Memory: State of the Science, a Review - Koerich Rondon, Tatiana; Maria Braga Tomitch, Lêda (Signo, 2022)
Working memory (WM) is a cognitive system that enables the simultaneous manipulation and storage of information, allowing the accomplishment of everyday activities, from the simplest to the most complex ones. Given its relevance, WM has been a prolific topic of study in cognitive psychology and related sciences. Several researchers have developed models to explain how WM is organized, how it interacts with other cognitive systems, how it supports processing and maintenance functions, among diverse specificities. From the first theoretical framework proposed by Baddeley and Hitch (1974) until today, research has advanced quite substantially based on various data sources such as behavioral, cognitive, neuroimaging, and computer modeling studies. After twenty-two years since the publication of the book entitled “Models of Working Memory: Mechanisms of Active Maintenance and Executive Control”, edited by Miyake and Shah (1999), Logie, Camos, and Cowan invited proponents of competing WM models to answer a series of questions in their new book entitled ‘Working Memory: State of the Science’ aiming to provide a comprehensive and integrative account of the current scenario.